Preparation of nano-structural Mn02 in ethanol-water media coated on calcinated laterite and study of its arsenic adsorption capacity - Loan, Dong Kim; Con, Tran Hong; Thuy, Le Thu (VNU Journal of Science: Natural Sciences and Technology, 2008)
Abstract